Expression of aminopeptidase N/CD13 in human ovarian cancers. Issue 5 (1st September 2006) - Surowiak, P.; DrĄG, M.; Materna, V.; Suchocki, S.; Grzywa, R.; SpaczyŃSki, M.; Dietel, M.; Oleksyszyn, J.; Zabel, M.; Lage, H.
Abstract : Aminopeptidase N/CD13 (EC 3.4.11.2) is suggested to play a role in cancer cells invasion, and its activity can be inhibited using specific inhibitors. CD13 inhibitors evoke apoptosis of CD13-positive cancer cells. However, expression of CD13 has not been described in specimens obtained from ovarian carcinomas. Thus, in the present study, the expression of CD13 and its significance was examined in samples of ovarian cancers. The analyses were performed on sections originating from 73 tumor samples (43 from primary laparotomies [PL] and 30 from secondary cytoreductions [SCRs]). Immunohistochemical reactions were performed on paraffin sections of studied tumors, using monoclonal antibodies against CD13. The analysis demonstrated no relationships between the expression of CD13 on one hand and clinical variables and pathologic variables of the patients on the other hand. Expression of CD13 was demonstrated to be significantly more pronounced in samples obtained in PLs as compared to samples from SCRs ( P < 0.001). Thus, the data indicate that a potential treatment of ovarian carcinoma with CD13 inhibitors should be performed before chemotherapy or in parallel to first-lapse chemotherapy.